Pertussis: clinical and bacteriological diagnosis of six cases - Arellano Penagos Mario; Aranda Patrón Eduardo; López Sotomayor Laura L. (Instituto Nacional de Pediatría, 2014)
ertussis is an endemic disease in our population. Every 3 to 4 years, pertussis has an epidemic pattern even in countries with good health conditions. Antipertussis vaccine first dose is adminis- tered at the age of 2 months; a second and third dose are given at 4 and 6 months of age. This vaccine has an 8 to 10 year protective effect, for which reason it is suggested that pregnant women in the third trimester should be vaccinated in order to prevent pertussis in newborns. It should also be administered to older people to avoid turning them into asymptomatic carriers. Clinic manifestations are easily identifiable due to respiratory symptoms, especially to the particular characteristics of the cough. The diagnosis is supported by the presence of leukocytosis (predominantly lymphocytes) and by certain thoracic radiologic findings. The diagnosis is confirmed with a positive culture for Bordetella pertussis or with a polymerase chain reaction (PCR). In a non complicated clinic course macrolides are still the best therapeutic choice. Nonetheless clinic observation is highly recom- mended in order to avoid complications. Redefinition of vaccine programs against Bordetella pertussis in Mexican population is recommended and also to notify the presence of the disease to the corresponding health authorities.